Catalytic asymmetric dearomatization (CADA) reactions of phenol and aniline derivatives. (22nd January 2016) - Wu, Wen-Ting; Zhang, Liming; You, Shu-Li
Abstract : In this tutorial review, an up to date summary of recent progress in catalytic asymmetric dearomatization (CADA) reactions of phenol and aniline derivatives is presented. Abstract : Phenols are widely used as starting materials in both industrial and academic society. Dearomatization reactions of phenols provide an efficient way to construct highly functionalized cyclohexadienones. The main challenge to make them asymmetric by catalytic methods is to control the selectivity while overcoming the loss of aromaticity. In this tutorial review, an up to date summary of recent progress in CADA reactions of phenol and aniline derivatives is presented.